2020
DOI: 10.1186/s13041-020-00586-5
|View full text |Cite|
|
Sign up to set email alerts
|

Ascending noradrenergic excitation from the locus coeruleus to the anterior cingulate cortex

Abstract: Anterior cingulate cortex (ACC) plays important roles in sensory perception including pain and itch. Neurons in the ACC receive various neuromodulatory inputs from subcortical structures, including locus coeruleus noradrenaline (LC-NA) neurons. Few studies have been reported about synaptic and behavioral functions of LC-NA projections to the ACC. Using viral-genetic method (AAV-DIO-eYFP) on DBH-cre mice, we found that LC-NA formed synaptic connections to ACC pyramidal cells but not interneurons. This is furthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Other differences in target area receptor-recruitment as a function of activation frequency have also been described. Koga et al. (2020) compared 1 min of 5-Hz or 20-Hz light trains on LC fibers entering anterior cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Other differences in target area receptor-recruitment as a function of activation frequency have also been described. Koga et al. (2020) compared 1 min of 5-Hz or 20-Hz light trains on LC fibers entering anterior cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…LC-NAergic neurons also send ascending projections throughout the brain that modulate several key brain functions [ 38 , 40 ]. Recently, it was reported that the activation of LC-NAergic neurons that project to the anterior cingulate cortex induces scratching behaviors [ 41 ]. Thus, it is possible that ascending and descending LC-NAergic neurons play a distinct role in the control of itch behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The brain was then removed and dehydrated with 30% sucrose overnight at 4 C. Transverse sections (30 mm) of brain samples containing the ACC and PVN were immunostained with GFP IgG (1:500, ab5450, Abcam) conjugated Alexa 488 conjugated donkey anti-goat IgG (1:1000, ab150133, Abcam). ACC areas were then observed under confocal microscope (Fluoview FV1000, Olympus, Tokyo, Japan) under appropriate filter for Alexa 488 for checking PVN-ACC projecting fiber expression (Chen et al, 2018;Koga et al, 2020).…”
Section: Optogeneticsmentioning
confidence: 99%